Islamic Economic Law as Fiqh Muamalah Iqtishadiyyah, Not from Conventional Economic Science - Joko Dwi saputro; Jumino Jumino; Hendrianto Hendrianto (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
This research aims to explore Islamic economic law, such as Fiqh Muamalah Iqtishadiyyah, which is different from conventional economics. Using qualitative methods, this research examines the concepts, principles and applications of Islamic economic law through literature analysis and in-depth interviews with experts in the field. Fiqh Muamalah Iqtishadiyyah offers a unique perspective rooted in the teachings of the Quran and Hadith, emphasizing ethics, justice and balance in economic activities. The research found that Islamic economic law not only focuses on material aspects but also considers economic transactions' moral and social implications. The results of this study show that the Fiqh Muamalah Iqtishadiyyah approach provides a holistic and sustainable alternative to the conventional economic model, often dominated by worldly and practical principles. As such, this research contributes to a deeper understanding of the role and potential of Islamic economic law in creating a more just and sustainable economic system.